Aspect angle dependence of naturally enhanced ion acoustic lines. Issue 7 (22nd July 2014) - Akbari, H.; Semeter, J. L.
Abstract The magnetic aspect angle dependence of naturally enhanced ion acoustic lines (NEIALs) is investigated using two multibeam experiments with the 450 MHz electronically steerable Poker Flat Incoherent Scatter Radar. In each experiment, dynamics in the accompanying auroral activity suggest that the source of free energy for the instability is equally present, in a statistical sense, in a wide portion of sky. Yet strong variations in backscattered power are observed when radar beam direction is altered by only 1°. In our observations, the strongest scattered power appears in the magnetic‐zenith direction and weakens with increasing angle between the radar beam and the magnetic lines of force. NEIALs occurring above the F region peak are observed to disappear almost completely at aspect angles as small as 2°. The results are somewhat surprising since previous experiments have detected NEIALs at aspect angles up to 15°. It is shown that during dynamic geophysical conditions, such as the substorm intervals studied in this report, more than one of the generation mechanisms proposed to explain NEIALs may be operating simultaneously. The different mechanisms result in different spectral morphologies and different degrees of sensitivity to the magnetic aspect angle.